THE NILE DELTA – WATER INSENSITIVE? (2014)
ABSTRACTThe Nile Delta is considered one of the deltas most vulnerable to climate change worldwide. Apart from the immediate threat of sea level rise it is additionally facing water scarcity, agricultural and ecological degradation in parallel to an unprecedented population increase and the vast urbanization of scarce agricultural land. The urbanization of the Nile Delta, which may be considered an even bigger threat than climate change, is dominated by informal building processes mainly for the lower income sector while the formal sector is planning new cities in the desert. To overcome the pressure of land scarcity in the Nile Valley and Delta, which make up only 4% of the country, the ongoing governmental strategy since the 1970s also for the delta’s fringes has been land reclamation in the desert, for both agricultural, industrial and settlement purposes. Yet, up until today “New Urban Communities” have not been able to attract the designated number of inhabitants as they fail to meet the needs of a large part of the population. Instead they have become market-steered recluses to a growing middle class that longs for a suburban life style and can afford it. Apart from offering a privileged lifestyle, desert developments are investment objects for the private sector. In the formally organized planning processes, sustainable design remains vanguard. As low-rise, high-density and mixed-use neighborhoods, informal developments evolving along canals and transportation nodes in the delta, meet a number of sustainability criteria. While these neighborhoods often lack proper infrastructure and safe accessibility internally, it is their location on scarce agricultural land that proves to be their main deficiency in the light of an increasing geographic vulnerability of the delta. In summary, currently both formal, market-steered developments on reclaimed desert land and informal developments in the Nile Valley and Delta lack ecological awareness. To become more resilient, how can ecological intelligence of people and places be incorporated in this spectrum of formal and informal settlement processes? Water scarcity and quality stand at the top of the list when looking at Egypt today. An overview of current social and spatial conditions in the Nile Delta region and of planning practice in Egypt today depicts a highly complex condition. This paper proposes Water Sensitive Urban Design as a tool for both formal and informal urban developments to negotiate between social and topographical extremes to increase resilience of the Nile Delta and its adjoining desert developments.RESUMENEl delta del Nilo es considerado uno de los deltas más vulnerables al cambio climático en todo el mundo. Además de enfrentarse a la amenaza inmediata del aumento del nivel del mar, debe hacer frente a la escasez de agua, la degradación de la agricultura ecológica y al aumento de población sin precedentes, impulsado por la urbanización de tierras agrícolas. La urbanización del delta del Nilo, que puede ser considerada una amenaza aún más grande que el cambio climático, está dominada por los procesos de construcción informal (principalmente en el valle y el delta, orientado al sector de menores ingresos), y formal (orientada a la planificación de nuevas ciudades en el desierto). Para superar la presión de la escasez de tierras en el valle del Nilo y el delta, que representan solo el 4% del territorio nacional, la estrategia gubernamental desde la década de 1970 ha sido la recuperación de tierras en el desierto tanto para agricultura como para la industria y residencia. Sin embargo, hasta hoy las nuevas comunidades urbanas no han sido capaces de atraer el número deseado de habitantes, ya que no son capaces de satisfacer las necesidades de una gran parte de la población. En la actualidad, ambos desarrollos, sean los formales, dirigidos al mercado en tierra desértica recuperada y los informales en el valle del Nilo y el delta, carecen de conciencia ecológica. Para incrementar la resiliencia ¿cómo puede la inteligencia ecológica de las personas y los lugares incorporarse como una solución en este espectro de procesos formales e informales? La escasez de agua y la calidad se sitúan en la parte superior de la lista cuando se mira en el Egipto de hoy. Una visión general de las actuales condiciones sociales y espaciales en la región del delta del Nilo y de la planificación de la práctica en Egipto hoy en día representa una condición muy compleja. En este trabajo se propone el Water Sensitive Urban Design como herramienta para el desarrollo urbano, tanto de los desarrollos formales como informales, para negociar entre los extremos sociales y topográficos y para aumentar la capacidad de recuperación del delta del Nilo y sus desarrollos desérticos.